As estratégias discursivas e a evolução do sujeito poético feminino: de Adélia Prado a Maria Lúcia Dal Farra - Teresa Cabañas (Universidade de Brasília, 2010)
This text aims at building a line of communication between Adélia Prado’s poetry, beginning with Bagagem (1976), and Maria Lúcia Dal Farra’s Livro de auras (1994). The intention is set on observing how the writers’ discursive strategies, in addition to revitalizing the local poetry code, suggest changes to the status of historical and social condition of female agents producing poetry. It is believed that this may indicate an expansion of the Brazilian poetry course, as well as showing an evolution path of that feminine entity as a social being within the historical circumstances of her existence.